2015
DOI: 10.1590/1678-69712015/administracao.v16n5p127-160
|View full text |Cite
|
Sign up to set email alerts
|

Marketing De Relacionamento (Crm): Estado Da Arte, Revisão Bibliométrica Da Produção Nacional De Primeira Linha, Institucionalização Da Pesquisa No Brasil E Agenda De Pesquisa

Abstract: RESUMOJá é consensual entre os principais autores da área de customer relationship management (CRM) ou marketing de relacionamento, a relevância da gestão estratégica do relacionamento entre as organizações e seus clientes, especialmente em um contexto de competitividade recrudescente. Destarte, este estudo enseja desenhar um panorama dos estudos sobre CRM, apresentando os resultados de uma revisão bibliométrica que abrange sínteses do estado da arte e dos estudos empíricos produzidos em periódicos nacionais d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
3
10
0
5
Order By: Relevance
“…Relationship marketing represents a paradigm change from the classical concepts of transactional marketing to an approach based on the 'conquest and enchantment' of customers (Grönroos, 1994;Sharma & Sheth, 1997). The studies on relationship marketing can be framed as B2C relationships or among organizational dyads (B2B) (Demo et al, 2015). In the latter, relationships among companies belonging to distribution channels and other types of relationships among companies that involve buying decisions are included (Rocha & Luce, 2006).…”
Section: B2b Marketingmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationship marketing represents a paradigm change from the classical concepts of transactional marketing to an approach based on the 'conquest and enchantment' of customers (Grönroos, 1994;Sharma & Sheth, 1997). The studies on relationship marketing can be framed as B2C relationships or among organizational dyads (B2B) (Demo et al, 2015). In the latter, relationships among companies belonging to distribution channels and other types of relationships among companies that involve buying decisions are included (Rocha & Luce, 2006).…”
Section: B2b Marketingmentioning
confidence: 99%
“…On this occasion, only 11 publications from EnANPADs and 9 publications from journals were found. More recently, three literature reviews (Almeida, Lopes, & Pereira, 2006;Demo, Fogaça, Ponte, Fernandes, & Cardoso, 2015;Faria, Giuliani, Pizzinatto, & Spers, 2014) have completely focused on relationship marketing and found that B2B was the second most researched theme, after B2C.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, database research indicates that most of the studies on relationship marketing have been developed in the business-to-consumer (B2C) context, while the smallest portion of the studies have been developed in the business-to-business (B2B). In this sense, bibliometric surveys of the national literature, which analyzed the period between 1990 and 2013, indicated that 2/3 of the studies have been carried out in the B2C context, while 1/3 of the studies have been carried out in the B2B context (Almeida, Lopes & Pereira, 2006, Coelho & Reinaldo, 2014, Faria, Giuliani, Pizzinatto & Spers, 2014, Demo, Fogaça, Ponte, Fernandes & Cardoso, 2015.…”
Section: Introductionmentioning
confidence: 99%
“…The bibliometric review considered articles published in national journals, with a classification of intellectual production, according to Qualis da Capes (Coordination for Improvement of Higher Education Brazilian scientific production Personnel), in the evaluation of Public Administration and Business, Accounting and Tourism, in stratum equal to or greater than B1. The cut was made in this stratum because it is the criterion used by most postgraduate programs in administration to evaluate firstline production (Demo et al, 2015) This article is organized into five parts, in addition to this introduction. Section 2 presents the theoretical framework for innovation, which will be important for the analysis of the following sections.…”
Section: Introductionmentioning
confidence: 99%